IMPLEMENTASI TEHNOLOGI INFORMATIKA YANG BERKEADILAN TERHADAP NASABAH BANK PERKREDITAN RAKYAT DALAM ERA DIGITALISASI - Gunherani, Dewi; Astuti, Widiyanti Rahayu Budi; Niagara, Serena Ghean (Gapenas Publisher, 2025)
This study aims to examine the obstacles to the implementation of digital information technology in Rural Credit Banks (BPR) and Sharia Rural Credit Banks (BPRS) within the framework of legal protection for customers in the era of the Industrial Revolution 5.0. Using a normative and empirical legal approach, this study combines banking regulation analysis with field findings through interviews and observations at several BPR/BPRS in the Jabodetabek, Banten, and West Java regions. The research findings indicate that the main obstacles lie in the limitations of core capital as per POJK, low digital literacy among customers, limited human resources in technology, inadequate digital infrastructure, insufficient incentives and strategic partnerships, and high vigilance toward legal risks and data breaches. This study concludes that the success of BPR/BPRS digitalization requires not only internal readiness but also affirmative support from regulators and inclusive strategies to improve digital literacy and data security. The implications of these findings highlight the need for differentiated policies and special incentives for microfinance institutions to prevent them from being left behind in the national digital transformation.